Uma Teoria Política Histórica: O Republicanismo Comtiano - Gustavo Biscaia de Lacerda (Mediações: Revista de Ciências Sociais, 2022)
This article presents the political theory proposed by Augusto Comte, also indicating his historical inspiration, in theoretical, political and epistemological terms. For Comte, knowledge is historical, in the sense that a cumulative theoretical and methodological elaboration is required so that reality can be known; on the other hand, sociological theorization requires the understanding of this historicity, which results in an epistemological and political relativism. These elements, among others, support the Comtian republicanism, understood as a human, secular, rational and altruistic regime. The republic is the regime that enshrines the common good and is the political realization of “sociocracy”, the social organization proper to positive modernity. The article has a theoretical character, based on direct consultation with Comtian texts and on secondary interpretative literature.